PEMAHAMAN KAUM IBU TENTANG STUNTING DAN DAMPAKNYA TERHADAP ASUPAN GIZI ANAK BALITA - De Gomes, Fransiskus; Petrus Redy Partus Jay (JURNAL SIPAKALEBBI, 2023)
The prevalence of stunting among toddler in NTT Province remains quite high. One factor contributing to the high incidence of stunting is the lack of understanding among mothers. This study aims to describe mothers’ comprehension of stunting and its impact on the growth and development of young children. The research employs a descriptive qualitative research method. The respondence of this study consist of 30 mothers with various educational backgrounds from Bangka Nekang Village and Wali Village, Langke Rembong District, Manggarai, NTT. Among these 30 mothers, eight of them have children who is experiencing stunting. The study was conducted between January 10th and April 16th, 2023. Research data were collected using questionnaires, interviews, and documentation. Data validity test was carried out using triangulation techniques. Data analysis employed Miles & Huberman’s analytical techniques. The results of the data analysis revealed that respondents have not fully understood stunting. There are 64.28% of respondents comprehend five aspects of stunting, including: failure to thrive in children, good child-rearing practices for toddler, diarrhea prevention, regular attendance at integrated health service posts for young children, and measuring height, weight, and head circumference in children. Other aspects of stunting have not yet understood by mothers involve ideal nutritious food composition, the benefits of breast milk (ASI) for children’s growth and development, the causes of stunting, and stunting prevention methods. Such understanding impacts the pattern of providing nutritious food for children. Food provision for children adheres to the child’s preferences, such as offering instant food within the culture of obligatory three meals per day without considering the nutritional composition of the child’s meals.Keywords: Understanding; Stunting; Nutritional Intake; Child Growth.